Secure key distribution using an ultra-long fiber laser with bi-directional EDFA - Soares Beatriz; Guerreiro Ariel; Frazão Orlando (EPJ Web of Conferences, 2022)
In this paper we describe the implementation of a secure key distribution system based on an ultra-long fiber laser with a bi-directional erbium doped fiber amplifier. The resilience of the system was tested against passive attacks from an eavesdropper, having been observed a similarity in spectrum for both secure configurations of the system.